Influence of steel–concrete bond damage on the dynamic stiffness of cracked reinforced concrete beams. Issue 13 (October 2018) - Xu, Tengfei; Huang, Jiantao; Castel, Arnaud; Zhao, Renda; Yang, Cheng
In this article, experiments focusing at the influence of steel–concrete bond damage on the dynamic stiffness of cracked reinforced concrete beams are reported. In these experiments, the bond between concrete and reinforcing bar was damaged using appreciate flexural loads. The static stiffness of cracked reinforced concrete beam was assessed using the measured load–deflection response under cycles of loading and unloading, and the dynamic stiffness was analyzed using the measured natural frequencies with and without sustained loading. Average moment of inertia model (Castel et al. model) for cracked reinforced beams by taking into account the respective effect of bending cracks (primary cracks) and the steel–concrete bond damage (interfacial microcracks) was adopted to calculate the static load–deflection response and the natural frequencies of the tested beams. The experimental results and the comparison between measured and calculated natural frequencies show that localized steel–concrete bond damage does not influence remarkably the dynamic stiffness and the natural frequencies both with and without sustained loading applied. Castel et al. model can be used to calculate the dynamic stiffness of cracked reinforced concrete beam by neglecting the effect of interfacial microcracks.